1997
DOI: 10.1093/ije/26.suppl_1.s49
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch EPIC food frequency questionnaire. II. Relative validity and reproducibility for nutrients

Abstract: The FFQ seems adequate for ranking subjects according to intake of energy, macronutrients, dietary fibre and retinol, but it does not yield such good results for beta-carotene, vitamin C for men, vitamin E for women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
264
2
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(299 citation statements)
references
References 19 publications
27
264
2
6
Order By: Relevance
“…Intakes of dietary fibre and most micronutrients, particularly vitamin A, obtained from FFQ have been shown to have lower correlations to the reference method compared with the macronutrients (20)(21)(22) , a trend also observed in the present study. Similar to other studies (23)(24)(25) , a low correlation was observed for vitamin E in the validation of the QFFQ against food diaries.…”
Section: Discussionsupporting
confidence: 80%
“…Intakes of dietary fibre and most micronutrients, particularly vitamin A, obtained from FFQ have been shown to have lower correlations to the reference method compared with the macronutrients (20)(21)(22) , a trend also observed in the present study. Similar to other studies (23)(24)(25) , a low correlation was observed for vitamin E in the validation of the QFFQ against food diaries.…”
Section: Discussionsupporting
confidence: 80%
“…Our assessment of alcohol, total energy, and protein intake has previously been shown to be reproducible [43]. However, the FFQ we used has been shown to underestimate total energy and protein intake as compared to basal metabolic rate and urinary nitrogen excretion used as reference methods, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…The self-administered food frequency questionnaire (FFQ) referred to habitual intake of 178 food items during the preceding year [42,43]. The questionnaire contained color photographs of 2-4 different-sized portions of 21 food items, which helped assessing the serving size.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, the portion size was different and we used portion sizes commonly used by Iranians. To mention other limitations, the methods used for dietary assessment are subject to variations (29,41) and therefore comparison between the two methods may not be precise; however, we evaluated the relative validity (42) to partly overcome this problem. Another limitation is that social characteristics, smoking and dietary supplement intake and BMI were not considered in our study.…”
Section: Discussionmentioning
confidence: 99%